Photochemical transformation of sulfadiazine in UV/Fe(II)/sodium citrate Fenton-like system. (15th November 2022) - Qin, Fangling; Zhang, Lin; Tong, Lei; Zhang, Kun; Nan, Wenzhao; Wang, Jingyi; Li, Menghan
Abstract: The persistence and potential hazards of antibiotics in the aquatic environment have attracted worldwide attention. Currently, advanced oxidation technology is considered to be an effective way to degrade antibiotics in the water environment. An enhanced photochemical Fenton-like system was investigated in this study for degradation of antibiotic sulfadiazine (SDZ). The degradation kinetics, pathways, and mechanisms of SDZ in four different photocatalytic systems were studied, including ultraviolet (UV), UV/sodium citrate (SC), UV/Fe(II), and UV/Fe(II)/SC. The highest degradation rate of SDZ was observed in UV/Fe(II)/SC system, and the complexation of SC-Fe(II) promoted photocatalytic efficiency and iron cycling. It was proved that hydroxyl radicals (OH) were generated in UV/Fe(II)/SC system, but excessive Fe(II) consumed OH and produced a UV shielding effect, thus reducing the degradation rate of SDZ. In the UV/Fe(II)/SC system, the degradation of SDZ followed pseudo-first-order kinetics, and the reaction rate constant of SDZ reached a maximum of 8.49 × 10 −3 min −1, with a degradation efficiency of 97.7%. Even in different real water samples, the removal rate of SDZ can reach about 80%. HCO3 −, SO4 2−, and NO3 − in the water environment inhibited the degradation of SDZ, and the order of inhibition was as follows: SO4 2−  > HCO3 − >NO3 − . With the increase of SDZ concentration and high concentration of humic acid (HA), the degradation rate of the target compound decreased. By identifying the photodegradation products of SDZ, four degradation pathways were proposed, and it revealed that the N–C bond and N–S bond were broken by attacking of hydroxyl groups, where a hydroxyl group replaced the H atom, resulting in the decomposition of SDZ into low molecular weight compounds like SO2, CO2, NO3 − and H2 O. It suggested that the UV/Fe(II)/SC system has good effect and application prospect in SAs treatment. Graphical abstract: Image 1 Highlights: Sulfadiazine can be degraded by UV/Fe(II)/SC system under neutral condition. Complexation of Fe-sodium citrate promotes photocatalytic efficiency and iron cycle. HCO3 −, SO4 2−, NO3 −, and humic acid can inhibit the photodegradation of sulfadiazine. Five degradation pathways of sulfadiazine are identified in photodegradation system.